Regeneration, growth and sustainability of mahogany in Mexico's Yucatan forests - Snook, Laura K. (Springer, 2003)
Big-leaf mahogany was studied on nine mixed-species stands that became established naturally between 2 and 75 years ago after catastrophic disturbances (hurricane blowdown, fire, or bulldozer clearing). More than 50% of adult big-leaf mahogany trees had survived a severe hurricane, leaving 2.8 seed trees ha-1. After fire, 29% to 100% of adult Mahogany trees survived, leaving an average of 1.4 seed trees ha 1. Thirty or more years later, postdisturbance mahogany trees were found at densities of 18 ha-1 after fire, as compared to 6 ha-1 after a hurricane. In mixed-species aggregations, mahogany trees grew at densities as great as 47 trees ha-1, accounting for up to 10% of the individuals and 27% of the basal area. A chronosequence of post fire stands to 15 to 75 years old revealed annual diameter increments ranging from more than 1 cm yr-1 between 15 and 30 years to 0.38 cm yr-1 between 45 and 75 years. Assuming constant growth, a big-leaf mahogany requires 122 years, on average, to reach the 55-cm minimum cutting diameter, although the fastest-growing trees may do so in 82 years. the current selective harvesting system, based on a 25-year cutting cycle, cannot be expected to ensure sustainable harvests of big-leaf mahogany because extraction exceeds growth and adequate regeneration conditions are not provided. Harvest rates should be reevaluated and efforts made to increase the harvest of other species and implement silvicultural treatments, or shifting agricultural systems should be integrated into the forest management regime to provide for the regeneration of this valuable shade-intolerant species.